1981
DOI: 10.4327/jsnfs1949.34.6_555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Protein on Plasma Lipoproteins and Liver Lipids in Cholesterol-fed Rats

Abstract: The effects of casein and soybean protein on plasma lipoproteins, apoproteins and liver lipids in cholesterol-fed rats were studied. 1) The diet composition for the standard group was (%): casein 20, corn oil 5, vitamin mix. 1, salt mix. 4, choline chloride 0.2 and corn starch to 100%. The control diet contained 0.5% of cholesterol and 0.3% of sodium cholate and 5% of lard replaced for corn oil. In rats given a control diet, the concentration of total cholesterol was higher in VLDL and LDL and lower in HDL2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

1983
1983
1985
1985

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…We also reported that when a diet was used containing 0.5% of cholesterol, the concentrations of plasma and liver cholesterol were lower in rats fed soybean protein than in those fed casein and HDL-cholesterol levels were higher in the soybean protein group (6). These data indicated the anti-atherosclerogenic activity of the.…”
supporting
confidence: 58%
“…We also reported that when a diet was used containing 0.5% of cholesterol, the concentrations of plasma and liver cholesterol were lower in rats fed soybean protein than in those fed casein and HDL-cholesterol levels were higher in the soybean protein group (6). These data indicated the anti-atherosclerogenic activity of the.…”
supporting
confidence: 58%
“…The effect of dietary protein on plasma cholesterol level has also been reported in the recent years (1-3). We observed that in the cholesterol-fed rats, high casein and soybean protein diet decreased plasma and liver cholesterol concentrations and increased high density lipoproteins (4). The difference of amino acid composition was demonstrated (5-8) but the presence of another unknown factor is considerable.…”
mentioning
confidence: 82%